Hookah Use Among US Youth: A Systematic Review of the Literature From 2009 to 2017. Issue 12 (28th June 2018) - Cooper, Maria; Pacek, Lauren R; Guy, Mignonne C; Barrington-Trimis, Jessica L; Simon, Patricia; Stanton, Cassandra; Kong, Grace
Abstract: Introduction: Given the US Food and Drug Administration (FDA)'s authority to regulate hookah, more research is needed to inform regulations intended to prevent youth from using hookah. This systematic review summarizes and assesses the literature related to hookah use among adolescents (11 to ≤18 years of age) in the United States from 2009 to 2017. Methods: Database searches yielded 867 peer-reviewed articles. After duplicates were removed, authors reviewed 461 articles for inclusion. Included articles ( n = 55) were coded for study themes, study quality, and their relevance to FDA's research priorities. A qualitative synthesis is presented. Results: The following themes were identified: (1) prevalence of hookah use ( n = 42), (2) tobacco use transitions ( n = 7), (3) sociodemographic correlates ( n = 35), (4) psychosocial risk factors ( n = 21), (5) concurrent use of other tobacco products ( n = 31), (6) concurrent use of other substances ( n = 9), and (7) other ( n = 15)—which includes low prevalence themes. The qualitative synthesis showed increasing rates of hookah use. Older age, male gender, positive social normative beliefs, higher peer use, as well as lower perceived risk were associated with hookah use. Longitudinal studies of youth hookah use showed bidirectional relationships between use of hookah and other tobacco products. All articles fell within FDA's research priority related to "behavior, " and three priorities ("impact analysis, " "health effects, " and "toxicity") have not been explored for hookah use among US youth since 2009. Conclusions: The prevalence of hookah use among youth in the United States is increasing, thus more research is needed to inform policies targeted to protect this vulnerable population. Implications: This study represents a novel contribution to our understanding of hookah use among youth in the United States from 2009—the year that the Family Smoking Prevention and Tobacco Control Act was passed—to 2017. In recent years, hookah has become a more popular tobacco product among US youth; however, to date, no systematic reviews of hookah use among this population exist. Results highlight implications for future US FDA regulatory policy and identify gaps in research to be addressed in future studies.